Presence of Beania mirabilis Johnston in the Gulf of San Matías (Argentina), with a key to the Argentine species of Beania (Bryozoa, Cheilostomatida) - López Gappa, Juan José (2001)
Beania mirabilis Johnston is recorded for the first time in Argentina. It was found on bivalve shells and polychaete tubes in the intertidal and subtidal zones of the Gulf of San Matías (40º46’S, 64º55’W), province of Río Negro, Argentina). This record increases in more than 16º of latitude its southern distribution limit in the southwest Atlantic Ocean. An illustrated key for the identification of the eight species of Beania known for the Argentine Sea is included.